Community, tools, and practices in web archiving: The state‐of‐the‐art in relation to social science and humanities research needs - Dougherty, M; Meyer, E (Wiley, 2014)
The web encourages the constant creation and distribution of large amounts of information; it is also a valuable resource for understanding human behavior and communication. To take full advantage of the web as a research resource that extends beyond the consideration of snapshots of the present, however, it is necessary to begin to take web archiving much more seriously as an important element of any research program involving web resources. The ephemeral character of the web requires that researchers take proactive steps in the present to enable future analysis. Efforts to archive the web or portions thereof have been developed around the world, but these efforts have not yet provided reliable and scalable solutions. This article summarizes the current state of web archiving in relation to researchers and research needs. Interviews with researchers, archivists, and technologists identify the differences in purpose, scope, and scale of current web archiving practice, and the professional tensions that arise given these differences. Findings outline the challenges that still face researchers who wish to engage seriously with web content as an object of research, and archivists who must strike a balance reflecting a range of user needs.